Particle Directional Conveyance under Longitudinal Vibration by considering the Trough Surface Texture: Numerical Simulation Based on the Discrete Element Method - Huazhi Chen; Shengyuan Jiang; Rongkai Liu; Weiwei Zhang (Shock and Vibration)
Particles can move directionally in a trough with finlike asperities under longitudinal vibrations. Here, we present an analysis of the particle conveyance mechanism and the influence of the asperity shape on the particle conveyance capacity by employing a numerical simulation based on the discrete element method (DEM). A dynamic-static matching method is proposed to characterize the three microcontact parameters in the simulation: the restitution coefficient, static friction coefficient, and rolling friction coefficient. The simulation shows that the asymmetric force induced by the finlike asperities and its cumulative effect over time lead to the particle directional conveyance. The conveyance velocity increases with increasing vibration time and is related to the median coordination number. The asperity height and slope inclination angles determine the trough shape and distance between two asperities directly. An undersized or oversized distance reduces the steady conveyance velocity. We find the optimal distance to be between one and two particle diameters.